Delayed cerebritis after bilateral stereotactic implantation of globus pallidus interna electrodes for treatment of dystonia. (1st February 2013) - Jankowski, Pawel P; Lessig, Stephanie; Nguyen, Andrew D; Barba, David
Abstract : Deep brain stimulation (DBS) is being used to treat an increasing number of movement and psychiatric disorders. However, the risk of infection remains as a problem that can hinder the usefulness of this technology. We report a case of a patient with dystonia who underwent bilateral globus pallidus interna electrode and impulse generator (IPG) placement, developed an infection of his IPG, and later cerebritis. The patient was initially treated with antibiotics and partial hardware removal. Follow-up cranial imaging showed an area concerning for cerebritis around one of the intracranial electrodes. The patient was then treated with complete hardware removal followed by a course of intravenous antibiotics. Four-month follow-up imaging showed resolution of the infection. This case demonstrates the importance of following cranial imaging in DBS patients with delayed infection, continued vigilance for infection in implanted patients and that partial hardware removal may not be successful in the setting of methicillin-sensitive Staphylococcus aureus infections.